Penyelesaian Sengketa Tanah (Adat) Suku Korowai - Buta Yaluwo; Simon Abdi K. Frank (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
The purpose of this article is to describe and analyze the mechanism for resolving customary land disputes in the Korowai tribe. The research method used is the approach used in this study is a qualitative descriptive approach. The location of this research was determined in Yanimura District, Boven Digoel Regency. Because of the considerations in that place there are always land disputes. The data collection process used was observation, interviews and FGD. And the data analysis process includes stages, data categorization, data description and data interpretation. The results show that land has an important meaning in the culture of the Koroeai tribe because it is related to values and sources of life. Disputes (ownership) of land that occur are often spearheaded by claims from 2 different owners, and because of differences in the determination of the boundaries of customary land ownership that is communally owned by clans, or certain communities. Settlement of customary land disputes of the Korowai tribe can be resolved by the customary parties as well as possible to mediate between the two warring parties. Then, a system of sanctions in the form of fines is given to parties who are considered detrimental to other parties.